Adsorption and removal of seven antibiotic compounds present in water with the use of biochar derived from the pyrolysis of organic waste feedstocks. Issue 5 (October 2021) - Stylianou, Marinos; Christou, Anastasis; Michael, Costas; Agapiou, Agapios; Papanastasiou, Panos; Fatta-Kassinos, Despo
Abstract: Biochars produced from various organic waste feedstocks have lately been utilized as adsorbents for the decontamination of antibiotics-contaminated environmental matrices. The aims of the present study were a) the assessment of the adsorption capacity of three distinct derived biochars [biosolids (BDΒ), cattle manure (MDB) and spent coffee grounds (SCGDB)], applied either at a low (1 g L −1 ) or high (10 g L −1 ) dose on seven antibiotics (tetracycline, TET; erythromycin, ERY; clarithromycin, CLA; ampicillin, AMP; ofloxacin, OFL; sulfamethoxazole, SMX; trimethoprim, TMP) spiked as mixture in environmentally relevant concentration (100 μg L −1 ) of an aqueous solution (8.27 < pH < 10.48), and b) the understanding of the relative adsorption mechanisms. Batch sorption experiments showed that all biochars applied at the low dose efficiently removed more than 70%, reaching even 100%, of TET, ERY, CLA, whereas MDB also removed AMP. Biochars applied at the high dose (10 g L −1 ) exhibited enhanced adsorption capacity, resulting in the quick (within 5 min of incubation) and complete removal of TET, ERY, CLA, as well as increased removal (>85%) of AMP and TMP. However, the studied biochars failed to remove OFL and SMX. The adsorption results were best fitted to the Freundlich model with the sole exception of SMX. The main responsible mechanisms for the adsorption of antibiotics included surface complexation, H-bonding, π-π electron-donor-acceptor (EDA) interactions, pore-filling effects or the simultaneous occurrence of several of these mechanisms. Overall, the results highlighted the potential utilization of BDB, MDB and SCGDB for the decontamination of antibiotics-contaminated water bodies, while promoting the circular economy strategy. Graphical Abstract: ga1 Highlights: Biochar produced can effectively decontaminate antibiotics-contaminated solutions. The removal efficiency is greatly depended on the pH value of the medium. Biochars applied at the high dose (10 g L −1 ) exhibited enhanced adsorption capacity. The adsorption results were best fitted to the Freundlich model.